Frequência de irrigação e doses de hidrogel na produção de mudas de pitaia branca (hylocereus undatus) - Diógenes, Maria Fgênia Saldanha (Universidade Federal Rural do Semi-Árido, 2019)
Some factors can limit the initial development of the pitayas, emphasized the scarcity of water. Agricultural hydrogels can be used to enhance the retention and availability of water and nutrients in the soil. Therefore, the objective of this work was to evaluate the influence of irrigation frequency and hydrogel doses on the development of white pitaya (Hylocereus undatus) seedlings, in order to establish an interval in days between irrigations that provides better seedling development and to determine the dose hydrogel that reduces water consumption without impairing seedling development. The experiment was conducted in a greenhouse at the Agricultural Sciences Center of the Federal Rural University of the SemiArid (UFERSA). The treatments were distributed in random blocks (DBC) in a 4 x 4 factorial scheme. The treatments correspond to four hydrogel doses (0, 2, 4 and 6 g/plant of Biogel Hydro Plus) incorporated to the substrate and four irrigation frequencies (1, 3, 5 and 7 days). After 120 days, biometric characteristics, photosynthetic pigments, organic and inorganic solutes of the plants were evaluated. It was concluded that the use of daily irrigation had a negative influence on most of the analyzed variables of the pitaya seedlings, which had greater development when an irrigation frequency of around three days was used. For the test conditions, the application of 6 g plant-1 hydrogel provided the highest averages for the accumulation of dry biomass, photosynthetic pigments, organic and inorganic solutes. The incorporation with the hydrogel made it possible to increase the interval between irrigations in one day, without losses to the development of seedlings.
Keywords: Cactaceae; Estresse hídrico; Polímero hidroabsorvente; Produção de mudas; Cactaceae; Hydrical stress; Hydroabsorbent polymer; Seedling production; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA